The Exchange Rate Volatility Impact on Agricultural Trade: An Evidence From Indonesian Pepper Export - Permana, Bertha Lovita Dwi Intania; Suharno; Rifin, Amzul (Jurnal Manajemen & Agribisnis, 2022)
Pepper (Piper nigrum) is one of the most exported spices in Indonesia followed by cinnamon, cloves, and vanilla. Due to its strong dependency on international trade, Indonesian pepper exports are suspected to be prone to exchange rate volatility risks. Traditionally, exchange rate volatility is perceived to discourage exports. However, studies to date remain to provide an open question on whether volatile exchange rates discourage exports. This paper aims to examine the impact of exchange rate volatility on Indonesian pepper exports to its main trading partners from 2005 to 2019. Using gravity model and GARCH (1,1) for volatility measurement, the results reveal that Indonesian pepper exports are not affected significantly by exchange rate volatility. This is because Indonesia has been in the position as a net exporter of pepper where a majority of its production is consumed abroad and pepper only costs a small percentage of the total cost of food productions. Keywords: exchange rate volatility, GARCH (1,1), gravity model, Indonesian pepper trade, Indonesian spice